Development Of A Media Training Model ZETRAS (Zenkutsudachi Training Speed) To Increase The Speed Of Forward Stance In The Sport Of Karate - Adelia, Yenny; Rasendriya, Sabitha; Ashadi, Kunjung; Wijono; Widohardhono, Rachman; Daulay, Dio; Sidik, Risky; Hafidz, Abdul; Yeti, Fifit; Utami, Tri (Proceeding of International Joint Conference on UNESA, 2024)
The research aims to develop training aid to increase the speed of the heavy front stance in the karate can be called ZETRAS (Zenkutsudachi Training Speed). The method used in this research is R&D (Research and Development) using five stages, namely ADDIE. The population in this study were Inkanas Banyuwangi karate athletes with a sample of 35 athletes. The results of prestest and posttest data analysis obtained a value of sig = 0,000 < 0,05, while the results of the comfort of using the tool questionnare were 57% "Agree" and 37% "Strongly Agree". Based on the results of the research above, it can be concluded that there is an influence of training to increase the speed of the heavy front karate stance and it has proven to be comfortable for Inkanas Banyuwangi karate athletes to use.